Are the environment, social, and government performance affecting the firm’s value? - Melinda Malau (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
This study aims to gather empirical data regarding how Environment, Social, and Governance (ESG) Performance affects Firm Value. This study uses two sets of control variables selected from several financial ratios to support the ESG score. The first model is the research observation in the short term with the first set of control variables. The second model is long-term with a second set of control variables. The research sample comprises publicly traded companies on the Indonesia Stock Exchange with a sustainability history and documented ESG performance. This study compiles secondary data sources for ESG company performance scores from Refinitiv This research uses EViews version 12 statistical package for econometric analysis. This study with first-step variables showed that ENV and GOV significantly positively influence firm value. In addition, variable control DAR and CR significantly positively influence fair value. In Model 2, this study’s second-step variables showed that SOC and GOV significantly positively influence fair value. Variable control ROE and ROA have a significant positive influence on fair value. During the financial crisis, ESG performance reduced financial risks; in more normal circumstances, its role grew considerably. This highlights the importance of ESG performance during the crisis, using new and optimized data sets.